Homesickness : stories - Barrett, Colin, 1982- (Grove Press, 2022)
"When Colin Barrett's debut Young Skins was published, it swept up several major literary awards, and, in both its linguistic originality and sharply drawn portraits of working-class Ireland, earned Barrett comparisons to Faulkner, Hardy, and Musil. Now, in a blistering follow-up collection, Barrett brings together eight character-driven stories, each showcasing his inimitably observant eye and darkly funny style. A quiet night in a local pub is shattered by the arrival of a sword wielding fugitive; a funeral party teeters on the edge of this world and the next, as ghosts simply won't lay in wake; a shooting sees a veteran policewoman confront the banality of her own existence; and an aspiring writer grapples with his father's cancer diagnosis and in his despair wreaks havoc on his mentor's life. The second piece of fiction from a "lyrical and tough and smart" (Anne Enright) voice in contemporary Irish literature, Homesickness marks Colin Barrett out as our most brilliantly original and captivating storyteller."--